Failure of female sterilization at Ramathibodi Hospital: a 20-year review (1969-1988). - S. Intaraprasert (2018)
The Department of Obstetrics and Gynaecology, Ramathibodi Hospital, has offered female sterilization services since 1969. There were 30,856 cases of sterilization in the last 20 years. Thirty-seven women became pregnant following sterilization (0.12%). The failure rate after laparoscopic and minilaparotomy technique was 0.19 per cent and 0.20 per cent respectively, and the failure rate of postpartum sterilization was only 0.02 per cent. The failure occurred from 3 to 106 months after sterilization. The majority of intrauterine pregnancies occurred within 12 months, while ectopic pregnancy occurred at different periods. Ectopic pregnancies occurred in 18.9 percent of the failure cases. The ectopic pregnancy rate following laparoscopic and minilaparotomy technique was 0.05 and 0.03 per cent respectively. No ectopic pregnancy was found after failure of postpartum sterilization in this series.